Pemanfaatan Buah Mangrove sebagai Bahan Warna Alami Batik Studi Deskriptif pada Kelompok UMKM Batik Karimun Jawa Jepara Jawa Tengah - DS Drajad Wibowo; Teguh Thamrin; Yushinta Eka Farida; Santi Andriyani (Indonesian Journal of Humanities and Social Sciences, 2023)
Sustainable fashion, also known as eco-fashion, has emerged as a critical consideration for textile observers and business entities, including Micro, Small, and Medium Enterprises (MSMEs) involved in Batik production. The primary objective is to foster an environmentally friendly approach and mitigate waste pollution. This study focuses on the utilization of mangrove fruit as a natural dye for Batik in the Karimun Jawa region. Additionally, it explores the perceptions of Batik MSMEs regarding the adoption of natural coloring. A descriptive qualitative methodology was employed, utilizing observation and questionnaires as research instruments. The findings reveal key insights: 1) The natural coloring process for Karimun batik involves mordanting, extraction, dyeing, fixation, and drying through the nglorod process; 2) Three mixtures—lime, alum, and arbor—were employed for color fixation, resulting in faded (bright), rather intense, and dark colors, respectively; 3) Questionnaire results indicate that respondents possess a solid understanding and proficiency in the natural dyeing process. Furthermore, respondents express a commendable motivation not only for economic improvement but also for contributing to a sustainable environment by minimizing waste. This study contributes to the growing discourse on sustainable practices within the textile industry, emphasizing the importance of eco-friendly alternatives such as mangrove fruit-based dyes in traditional crafts like Batik. The insights gathered from Batik MSMEs' perceptions shed light on the potential for widespread adoption of sustainable practices in the broader context of textile production.